Great Britain 2026 - Bewley, Sarah; Hallett, Becca; Kenny, Stuart; Naylor, Claire; Williams, Christian (DK eyewitness., 2026)
Make your trip to Great Britain extraordinaryA road trip through historic market towns. Hiking in the Scottish Highlands. Visiting hundreds of world-class museums. There are so many reasons to visit Great Britain. Whatever your dream trip involves, this DK travel guide is the perfect companion.Our updated guide brings Great Britain to life, transporting you there like no other travel guide does with expert-led insights, trusted travel advice, detailed breakdowns of all the must-see sights, photographs on practically every page, and our hand-drawn illustrations, which take you inside the country's buildings and neighbourhoods.You'll discover:our pick of Great Britain's must-sees and top experiencesbeautiful photography and detailed illustrations, taking you to the heart of Great Britainthe best spots to eat, drink, shop and staydetailed maps and walks which make navigating the region easyeasy-to-follow itinerariesexpert advice: get ready, get around and stay safecolour-coded chapters to each part of Great Britaina lightweight format, so you can take it with you wherever you goWant the best of Great Britain in your pocket? Try our Top 10 guides to Scotland, the Lake District, Cornwall and Devon, and London.